New record of Trichopeltarion dextrum (Rathbun, 1898) (Brachyura: Trichopeltariidae) from Brazil - Viana, Girlene Fábia Segundo; Silva, Kátia C. A.; Cintra, Israel Hidenburgo Aniceto; Souza-Filho, Jesser F. (Zootaxa, 2023)
Trichopeltarion dextrum (Rathbun, 1898) is herein reported from the first time from Northern Brazil. The specimens were captured using the shrimp trawls during the REVIZEE–Score Program. Six specimens, being two males and four females, were examined. The material fits well with diagnostic characters of T. dextrum, but the males have the carapace almost as long as wide, while in the type material, is slightly longer the wide. This is the second species of the genus Trichopeltarion reported from Brazilian waters.